Artificial general intelligence : 11th International Conference, AGI 2018, Prague, Czech Republic, August 22-25, 2018, Proceedings /: 11th International Conference, AGI 2018, Prague, Czech Republic, August 22-25, 2018, Proceedings. (2018) - Unknown
No abstract available